Dietary supplementation of Bacillus subtilis and Enterococcus faecalis can effectively improve the growth performance, immunity, and resistance of tilapia against Streptococcus agalactiae. (31st May 2021) - Liu, Qian; Wen, Luting; Pan, Xianhui; Huang, Yin; Du, Xuesong; Qin, Junqi; Zhou, Kangqi; Wei, Zina; Chen, Zhong; Ma, Huawei; Hu, Tingjun; Lin, Yong
Abstract: The combined probiotics (four different combination of Bacillus subtilis, Bacillus licheniformis and Enterococcus faecalis ) were used and the growth performance, immunity, gut morphology and resistance to Streptococcus agalactiae of tilapia ( Oreochromis mossambicus ) were comprehensively evaluated after 42 days feeding on supplemented diets. Results showed that the growth performance of tilapia in PG2 (with B. subtilis and E. faecalis ) was the best. Moreover, the strong positive association of some indices with specific probiotics was demonstrated for lipase activity, SI, LYZ, C3, T‐AOC and CAT were higher in PG2, indicating that the specific probiotics, and not diversiform probiotics, were the key determinants of the results for tilapia. The better gut villi length, villi width and muscular thickness in fishes under PG2, which shows that specific probiotics can promote the good development of gut mucosal structure of tilapia. Over 76% survival rate for tilapias against S. agalactiae in the PG2 may be because the B. subtilis and E. faecalis provided a better gut micro‐ecological environment. Totally, B. subtilis and E. faecalis may be specific to tilapia gut microbes.